A comparative bibliometric analysis of the top 150 cited papers in hypospadiology (1945–2013). Issue 2 (April 2015) - O'Kelly, F.; Nason, G.J.; McLoughlin, L.C.; Flood, H.D.; Thornhill, J.A.
Summary Introduction Hypospadias, the most common congenital malformation of the penis, is characterized by an abnormal ventral opening of the urethral meatus, abnormal ventral curvature of the penis, and an abnormal distribution of the foreskin around the glans, with a ventrally-deficient hooded foreskin, and has been described in modern peer-reviewed literature since Noble's description in 1853. A dramatic increase in the literature on hypospadiology has focused on two main topics: The aetiology of the condition including molecular mechanisms and environmental influences, as well as surgical techniques to repair the defect, however there have been a number of facets of research stemming from this poorly understood condition in a developing subspecialty (Figure). The majority of these publications focus on the evolution of surgical technique and management. Urethral reconstruction should offer the ability to stand to urinate and combine a satisfactory cosmetic result. The tubularized incised plate repair, popularized by Snodgrass et al., and the Mathieu repair, have been the mainstay for distal hypospadias, however, there have still been a large number of well-described techniques, with no consensus as to the ideal method of repair, some of which is attributed to non-uniform standards of reporting outcomes. There is also no standard objective means to qualitatively assess the importance of each of these contributions. Objective The objective of this study was to determine the top 150 peer-reviewed articles in the field of hypospadiology by way of citation analysis as a means to determine the importance/relevance of each contribution throughout 8 decades of research. Study design A cited reference search was carried out for indexed citations within Web of Science™ Core Collection. The top 150 indexed cited articles containing the topic "hypospadias" in specific subject categories were compiled using a component of Science Citation Index command. References were then evaluated, and analysed across a number of indices, and over time. Results The mean number of citations was 76 for each article. The top 150 articles were published across 21 countries, with the majority originating from the USA. The lead research institution was the University of Texas (Southwestern) Medical Center. In total, the top 3 centers represented 33 publications within the top 150 citations. The most commonly utilized journal was the Journal of Urology. The most cited author was W.T. Snodgrass. 39% papers in the top 150 cited articles were published prior to 1990. Three out of the five papers cited in the 1940s dealt with operative technique to repair hypospadias. The period 2000–2010 in contrast, demonstrated a significant inverse correlation between molecular biology citations, and those for operative techniques, with the incidence of the latter dropping to 6% of all cited papers. Discussion This is the first study of its kind to analyse the most influential articles in hypospadiology, and their characteristics assessed for authorship, content and impact factor. Furthermore it allows data analysis by topic and between time points. This not only de-clutters the wealth of accumulated data on this subject, but also provides an important adjunct to education and training. As with this study, other citation analytical studies in urology found a significant preponderance in cited studies originating from the USA. The prevalence of the US in cited papers doesn't reflect any inherent bias, just a greater number of publications. Conclusion Although there are inherent potential elements of bias in citation analysis, this study demonstrates that citation analysis in a complicated topic can provide a high-throughput, uncomplicated method of quickly deciphering important contributions of authors and institutions to the field of hypospadias research.